Fractional Flow Reserve-Guided PCI or Coronary Bypass Surgery for 3-Vessel Coronary Artery Disease: 3-Year Follow-Up of the FAME 3 Trial - Zimmermann, Frederik M; Ding, Victoria Y; Pijls, Nico H J; Piroth, Zsolt; van Straten, Albert H M; Szekely, Laszlo; Davidavicius, Giedrius; Kalinauskas, Gintaras; Mansour, Samer; Kharbanda, Rajesh; Östlund-Papadogeorgos, Nikolaos; Aminian, Adel; et al. (Circulation, 2023)
BACKGROUND: Previous studies comparing percutaneous coronary intervention (PCI) with coronary artery bypass grafting (CABG) in patients with multivessel coronary disease not involving the left main have shown significantly lower rates of death, myocardial infarction (MI), or stroke after CABG. These studies did not routinely use current-generation drug-eluting stents or fractional flow reserve (FFR) to guide PCI. METHODS: FAME 3 (Fractional Flow Reserve versus Angiography for Multivessel Evaluation) is an investigator-initiated, multicenter, international, randomized trial involving patients with 3-vessel coronary artery disease (not involving the left main coronary artery) in 48 centers worldwide. Patients were randomly assigned to receive FFR-guided PCI using zotarolimus drug-eluting stents or CABG. The prespecified key secondary end point of the trial reported here is the 3-year incidence of the composite of death, MI, or stroke. RESULTS: A total of 1500 patients were randomized to FFR-guided PCI or CABG. Follow-up was achieved in >96% of patients in both groups. There was no difference in the incidence of the composite of death, MI, or stroke after FFR-guided PCI compared with CABG (12.0% versus 9.2%; hazard ratio [HR], 1.3 [95% CI, 0.98-1.83]; P=0.07). The rates of death (4.1% versus 3.9%; HR, 1.0 [95% CI, 0.6-1.7]; P=0.88) and stroke (1.6% versus 2.0%; HR, 0.8 [95% CI, 0.4-1.7]; P=0.56) were not different. MI occurred more frequently after PCI (7.0% versus 4.2%; HR, 1.7 [95% CI, 1.1-2.7]; P=0.02). CONCLUSIONS: At 3-year follow-up, there was no difference in the incidence of the composite of death, MI, or stroke after FFR-guided PCI with current-generation drug-eluting stents compared with CABG. There was a higher incidence of MI after PCI compared with CABG, with no difference in death or stroke. These results provide contemporary data to allow improved shared decision-making between physicians and patients with 3-vessel coronary artery disease. REGISTRATION: URL: https://www. CLINICALTRIALS: gov; Unique identifier: NCT02100722.
Keywords: Coronary Artery Disease; nemoci koronárních tepen; frakční průtoková rezerva myokardu; Humans; Coronary Artery Bypass; koronární angioplastika; Stroke; coronary artery bypass; následné studie; drug-eluting stents; lidé; infarkt myokardu; cévní mozková příhoda; koronární bypass; Myocardial Infarction; Percutaneous Coronary Intervention; Fractional Flow Reserve, Myocardial; percutaneous coronary intervention; Follow-Up Studies